2016
DOI: 10.17116/hirurgia2016434-39
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of intestinal malrotation in newborns and infants

Abstract: Our results showed that endoscopic correction of congenital anomalies of intestinal rotation provides better postoperative results than open surgery and can be widely used in young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Although a rapid postoperative recovery of peristalsis after laparoscopic surgery has been reported in many studies [ 8 , 11 , 13 ], we did not find that the laparoscopic group had a significant advantage in postoperative intestinal function recovery in our study as the other reports [ 14 , 15 ]. Our method of judging the recovery of bowel function is by the time of the first defecation after surgery.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Although a rapid postoperative recovery of peristalsis after laparoscopic surgery has been reported in many studies [ 8 , 11 , 13 ], we did not find that the laparoscopic group had a significant advantage in postoperative intestinal function recovery in our study as the other reports [ 14 , 15 ]. Our method of judging the recovery of bowel function is by the time of the first defecation after surgery.…”
Section: Discussioncontrasting
confidence: 82%
“…At the same time, we found that the operation time of laparoscopic surgery was longer than that of open surgery group. Many studies have the same opinion [ 13 , 16 , 17 ]. Our operation time is similar to the previous study [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…[24,25] Laparoscopy is more popular because it results in smaller wounds, less pain, less time in surgery, less blood loss during surgery, a shorter stay in hospital, and fewer problems than traditional laparotomy. [26][27][28][29][30] It is difficult to delay surgical exploration after the detection of pneumoperitoneum in patients exhibiting signs of illness and abdominal exam results indicating NEC, the most common cause of perforation, because it is vital to rule for visceral rupture. Pneumoperitoneum evaluation, on the other hand, follows a protocol developed by Karaman et al [27,28]that includes a thorough history of cardiopulmonary resuscitation (CPR), intubation and breathing, a physical exam to search for macrosiphum, as well as a number of diagnostic methods.…”
Section: Discussionmentioning
confidence: 99%